2021
DOI: 10.3390/nu13020624
|View full text |Cite
|
Sign up to set email alerts
|

AGREEing on Nutritional Management of Patients with CKD—A Quality Appraisal of the Available Guidelines

Abstract: Chronic kidney disease (CKD) is an important public health issue with increasing prevalence worldwide. Several clinical practice guidelines have been recently published regarding the nutritional management of CKD patients. The purpose of the present study is to evaluate the quality of the published guidelines and provide recommendation for future updates. PubMed, Scopus and Google Scholar were searched for relevant guidelines and 11 clinical practice guidelines were finally included. Guidelines developed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The AGREE II manual does not offer any advice on how to explain the scores. In accordance with previous studies (15,16), if a CPG scored above 70% on six domains, it was classified as 'high quality'; if a CPG scored above 70% on three to five domains, it was classified as 'moderate quality'; and if a CPG scored less than 70% on ≥ two domains, it was classified as 'low quality' .…”
Section: Quality Assessmentsupporting
confidence: 83%
“…The AGREE II manual does not offer any advice on how to explain the scores. In accordance with previous studies (15,16), if a CPG scored above 70% on six domains, it was classified as 'high quality'; if a CPG scored above 70% on three to five domains, it was classified as 'moderate quality'; and if a CPG scored less than 70% on ≥ two domains, it was classified as 'low quality' .…”
Section: Quality Assessmentsupporting
confidence: 83%
“…According to the calculation formula, the scores in each domain were calculated and the calculation formula was as follows: each domain score = (obtained score – minimum possible score)/ (maximum possible score – minimum possible score) × 100%. Consistent with a previous study ( 28 ), the score of a domain or overall rating ≤ 40% was considered as a low rating, >40 and ≤ 70% as a moderate rating, and > 70% as a high rating.…”
Section: Methodsmentioning
confidence: 81%
“…The authors also found that the nutritional care procedures recommended by different CPG varied greatly (8) . Recently, a quality appraisal review of eleven guidelines for the nutritional management of patients with chronic kidney disease showed that none of them presented high quality according to the AGREE II tool, while three presented moderate quality and were recommended with modifications by the reviewers (53) . To the best of our knowledge, no systematic review of nutrition CPG applied the AGREE-REX tool (11) .…”
Section: Quality Of Guidelines On Nutrition Care Processesmentioning
confidence: 99%